FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA INSTANSI PEMERINTAH KOTA SURABAYA - Banusu, Andrea Arneyani; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of budget preparation participation, human resource quality, internal control system, and the use of information technology to the performance of local government institution on the Local Apparaturs Working Unit of Surabaya city. The data is the primary data. The data has been collected by issuing questionnaires to the respondents. The total amount of the research samples are the entire employees on 17 Local Apparaturs Working Units of Surabaya city and the sample collection technique has been done by using purposive sampling and the 64 respondents in 17 Local Apparaturs Working Units of Surabaya city have been selected as samples. The criteria are: civil servant i.e. the accounting department staff and budgetary department staff. The data analysis has been carried out by using multiple linear regressions analysis and the SPSS 20.0 software for windows to process the questionnaire data. The result of the research shows that budget preparation participation, human resource quality, internal control system, and the use of information technology give positive influence to the performance of the Local Government institution.Keywords: Performance, human resources quality, information technology, budget, internal control system